2017
DOI: 10.1038/srep45149
|View full text |Cite
|
Sign up to set email alerts
|

Iron-based magnetic superhalogens with pseudohalogens as ligands: An unbiased structure search

Abstract: We have performed an unbiased structure search for a series of neutral and anionic FeL4 (L = BO2, CN, NO2, NO3, OH, CH3, NH2, BH4 and Li2H3) clusters using the CALYPSO (Crystal structure Analysis by Particle Swarm Optimization) structure search method. To probe the superhalogen properties of neutral and anionic FeL4 clusters, we used density-functional theory with the B3LYP functional to examine three factors, including distribution of extra electron, pattern of bonding and the nature of the ligands. Theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
(91 reference statements)
0
5
0
Order By: Relevance
“…By comparing the total and partial DOS, it is obviously found that the total DOS mainly come from the d-states of transition-metal Fe atoms, while the magnetic moments of pseudohalogens CN-s and CN-p states are almost negligible, suggesting that the spin polarization is mainly localized on Fe atoms. This result is in good agreement with the finding of mononuclear iron-based magnetic superhalogen. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing the total and partial DOS, it is obviously found that the total DOS mainly come from the d-states of transition-metal Fe atoms, while the magnetic moments of pseudohalogens CN-s and CN-p states are almost negligible, suggesting that the spin polarization is mainly localized on Fe atoms. This result is in good agreement with the finding of mononuclear iron-based magnetic superhalogen. , …”
Section: Resultsmentioning
confidence: 99%
“…The unbiased structure search is performed using the CALYPSO (Crystal structure Analysis by particle Swarm Optimization) method combined with B3LYP (Becke’s three-parameter hybrid exchange functional with the Lee-Yang-Par correlation) functional. It has been successfully used to predict the ground state structures of various systems. For neutral and anionic Fe 2 (CN) 5 and Fe 3 (CN) 7 clusters, the first generation of structures is produced randomly and subsequently optimized. Each generation contains 30 structures.…”
Section: Computation Detailsmentioning
confidence: 99%
“…In brief, it can explore the global minima of the potential energy surfaces of predicted system only based on the chemical compositions at given external conditions. It has achieved great success in predicting the ground-state structures of various systems 4449 . Herein, initial structures for Re 2 X 8 2− clusters are achieved by the CALYPSO method.…”
Section: Computational Methodsmentioning
confidence: 99%
“…To obtain the most stable structures of (BO 2 ) n ( n = 1–3) adsorbed on the silicene surface, we performed an unbiased global structure search using the CALYPSO code . This method can obtain the reasonable results if the chemical compositions are under the given conditions, which has been used in various systems successfully. For each type of (BO 2 ) 1–3 molecule adsorbed on silicene, 30 generations are followed to achieve convergence. Each generation contains 40 configurations, 60% of which are produced by particle swarm optimization (PSO), while the rest are generated randomly.…”
Section: Computational Detailsmentioning
confidence: 99%